Cardiorespiratory system state of sportsmen with different types of blood-circulation during physical load - Vanyushin, J. S.; Fedorov, N. A. (The Russian Journal of Physical Education and Sport, 2017)
Annotation.One of the peculiarities of heart activity is the types of blood-circulation. Nowadays it is stated that revealed in terms of blood-circulation rest types influence the reaction of cardiovascular system during physical load. Taking into consideration the point of view concerning the initial hemodynamic heterogeneity and the notion of different types of blood-circulation existence, the questions about educational-training process of sportsmen in different kinds of sport and of different age can be solved. Material. The state of sportsmen`s cardiorespiratory system determination as the reaction to the load of the increasing power depending on typological peculiarities of blood-circulation Research methods: scientific literature analysis and summarizing, the indices of cardiorespiratory system testing, methods of mathematical statistics. Results. Three kinds of blood-circulation were revealed among sportsmen. Most sportsmen belong to hypokinetic type of blood-circulation, other sportsmen have hyperkinetic type. Inotropic function of heart is higher in the group of sportsmen with hypokinetic type of blood-circulation and it is the most effective mechanism of urgent adaptation demonstration of a cardiac output to the load. Among the sportsmen with hyperkinetic and eukinetic types of blood-circulation the increase of cardiac output happens by means of chronotropic heart reaction. The values of respiratory minute volume in the groups of the respondents were achieved by different combinations of breathing frequency and respiratory capacity. On economic activity of respiration influenced the types of blood-circulation. Conclusion. During cardiorespiratory system study with the help of a complex of noninvasive research methods we offer to use a complex approach, which means simultaneous registration of cardiovascular and respiratory system indices. It will help to define typical regularities depending on the types of blood-circulation and the power of the fulfilled physical loads, judging by the prevailing character of the separate reactions from the organs of blood-circulation and respiration. Thus, even in cardiorespiratory system itself there are difficult adaptive interactions, which are demonstrated in diversity of different variants of reaction to physical load.